Estimating the disability adjusted life years associated with COVID-19 in Iran for the first 2 years of the pandemic - -Bokaie, Saied; Daneshi, Salman; Bahonar, Alireza; Haghdoost, AliAkbar; Barfar, Eshagh; Patrick Moran, Declan (Frontiers in Public Health, 2024)
Background The World Health Organization (WHO) declared a pandemic of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), on 11 March 2020. Disability-adjusted life years (DALYs) combine the impact of morbidity and mortality, allowing for comprehensive comparisons of the population. The purpose of this study was to estimate DALYs due to COVID-19 in Iran for the first 2 years of the pandemic. Methods DALYs were estimated as the sum of Years of Life Lost (YLLs) and Years Lived with Disability (YLDs) associated with COVID-19 in Iran from 19 February 2020 to 20 March 2022. The life expectancy for COVID-19 YLL estimations was based on the Global Burden of Disease (GBD) 2019 study. Results There were 15,639,243 outpatients and 1,170,602 hospitalized confirmed cases, of which 120,965 deaths were as a direct result of COVID-19. DALYs were estimated to be 2,376,552. Overall, YLL contributed to 99.34% of the DALYs, while the remaining 0.66% was attributed to YLD. Conclusion COVID-19 had a significant impact on population health in Iran during the first 2 years of the pandemic; this study provides a comprehensive depiction of COVID-19’s burden and is helpful for comparing its impact with other diseases in the population and across populations.